2018
DOI: 10.6001/chemija.v29i4.3841
|View full text |Cite
|
Sign up to set email alerts
|

Herbal teas as a rich source of phenolic compounds

Abstract: Phenolic compounds are of a considerable interest and have received more and more attention in recent years due to their bioactive functions. These components are known as secondary plant metabolites and also possess antimicrobial, antiviral and anti-inflammatory properties. The popular Latvian herbals – Calendula (Calendula officinalis L.), Lady’s-mantle (Alchemilla vulgaris L.), Yarrow (Achillea millefolium L.), Peppermint (Mentha × piperita L.) and Bellis (Bellis perennis L.) – are widely used for herbal te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…Individual phenol analysis. Individual phenols in brewed coffee samples were analysed using high-performance liquid chromatography (HPLC) as described by Augðpole et al (2018). The HPLC analysis was performed using a "LC-20 Prominence" chromatograph (Shimadzu USA Manufacturing Inc., USA) with a "Perkin Elmer C18" column (4.6 mm, -250 mm, 5 µm).…”
Section: Physical Parameter Analysismentioning
confidence: 99%
“…Individual phenol analysis. Individual phenols in brewed coffee samples were analysed using high-performance liquid chromatography (HPLC) as described by Augðpole et al (2018). The HPLC analysis was performed using a "LC-20 Prominence" chromatograph (Shimadzu USA Manufacturing Inc., USA) with a "Perkin Elmer C18" column (4.6 mm, -250 mm, 5 µm).…”
Section: Physical Parameter Analysismentioning
confidence: 99%
“…Marigold is known to have a rich composition including many bioactive compounds such as carotenoids [18], phenolic acids (protocatechuic, vanillic, syringic acids), hydroxycinnamic acids ( p -coumaric, caffeic, chlorogenic acids), and flavonoids and their glycosides (quercetin, isorhamnetin, isoquercitrin, rutin) [19,20]. Moreover, there are studies in the literature on the determination of the polyphenol content of Calendula officinalis L. by chromatographic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Kotb et al [19] reported that cinnamic acid, chrysin, rutin, caffeic acid, and syringic acid were identified in Calendula officinalis L. In another study, Frum [21] found gallic acid, cinnamic acid, syringic acid, ferulic acid, and rutin in the HPLC analysis of Calendula officinalis L. extracted through maceration. Augšpole et al [20] performed the characterization of phenolic contents present in five herbal tea infusions, including Calendula officinalis L., by HPLC. Phenolic compounds such as chlorogenic acid, 4hydroxybenzoic acid, gallic acid, and vanillin were detected in a Calendula officinalis L. infusion.…”
Section: Introductionmentioning
confidence: 99%
“…The thick character of herbal syrups also has a soothing effect on irritated tissues (Kausik et al, 2016). Fruits and herbs are used in many domains, including nutrition, beverages, cosmetics, medicine, fragrances, flavouring and dyeing (Augspole et al, 2018). Fruit and herbal are used by the most of the world's population.…”
Section: Introductionmentioning
confidence: 99%